Tetradecane producing biocontrol agent, Trichoderma spp. against Fusarium oxysporum in tomato (Solanum lycopersicum L.) - Pavirhra, R.; Lalitha, S. (International Journal of Agricultural Technology, 2020)
The secondary metabolites from Trichoderma harzianum - Tr01 and Trichoderma viride- Tr02 were extracted from liquid culture using ethyl acetate and tested for their activities against fungal pathogen, Fusarium oxysporum (Fuo4) causing wilt disease in tomato (Solanum lycopersicum L.). Two isolates of Trichoderma harzianum (Tr01), Trichoderma viride (Tr02) were antagonized F. oxysporum causing tomato wilt. T. harzianum Tr01 showed the highest chitinase activity of β-1-3-glucanase. The treated inoculated tomato with Trichoderma extract was investigated. Trichoderma harzianum (Tr01) showed strongest inhibitory activities against Fusarium oxysporum. T. harzianum (Tr01) found to produce Dodecane, tetradecane, Diethyl Phthalate, Hexadecane, Benzenepropanoic acid, 3,5- bis (1,1-dimethylethyl)-4-hydroxy-, methylester, n-Hexadecanoic acid, Tetracontane, Bis(2-ethylhexyl) phthalate, Tetracontane. It concluded that Trichoderma harzianum (Tr01), Trichoderma viride (Tr02) can be produced active metabolites to control Fusarium wilt of tomato. The bioinoculants of T. harzianum Tr01 and Trichoderma viride Tr02 was highly inhibited the tested plant pathogen and enhanced plant growth.